Pengaruh Ukuran Perusahaan, Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, dan Profitabilitas terhadap Nilai Perusahaan - Yetty Murni; Hotman Fredy; Savena Anugerahwati (Universitas Jember, 2018)
This research is to examine and analyze the impact of firm size, investment decision, funding decision, dividend policy, and profitability to value of the firm to the property, real estate and building constraction companies that is listing in Indonesian Stock Exchange (IDX) in the year of 2012-2016. This sample research is taken by purposive sampling technique, so as to get as many 17 samples of property, real estate, and building constraction companies that is listing in Indonesian Stock Exchange (IDX) in the year of 2012-2016. Analysis method that is used multiple linear regression. The result of the research is shown that funding decision, dividend policy and profitability is impacted to the value of the firm, while the firm size and investment decision is not impacted to the value of the firm. Keywords: firm size, investment decision, funding decision, dividend policy, profitability, the firm value, multiple linear regression